Strong convergence of modified Noor iterations - Yongfu Su; Xiaolong Qin (International Journal of Mathematics and Mathematical Sciences)
In this paper, strong convergence theorem is obtained for the modified Noor iterations in the framework of uniformly smooth Banach spaces. Our results extend and improve the recent ones announced by Wittman, Kim, Xu, and some others.